Sociodemographic Determinants of Personality Disorder In Patients of Obsessive-compulsive Disorder (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: Obsessive Compulsive Disorder (OCD) is the 4th most prevalent psychiatric disorder in Epidemiological Catchment Area (ECA) Survey and most individuals with OCD have co-morbid personality disorders (PD). The present study was undertaken to find the prevalence of PD among patients with OCD and the sociodemographic determinants that influence the development PD in patients with OCD.Methods:The cross-sectional analytical study was conducted in OCD clinic of Bangabandhu Sheikh Mujib Medical University from January 2015 to September 2016. Respondents were recruited from the OCD patients diagnosed on the basis of DSM-IV criteria and face to face interview was conducted with the help of the Structured Clinical Interview for DSM-IV Axis II Disorders (SCID-II questionnaire). The main outcome variable was PD in patients of OCD and the exposure variables (determinants) were selected sociodemographic characteristics.Result: The mean age of the OCD patients was (28 ± 8.7) years. Almost half (49%) of OCD patients belonged to the age group 20-30 years. Female respondents were 53.6%. Among the respondents, 62% had co-morbid PD. The mean age of the OCD patients with PD was observed to be significantly higher (29.1 ± 9.1 years) than those without PD (26.2 ± 7.8 years) (p = 0.047). Male OCD patients were 2.4 (95% CI of OR: 1.2 – 4.7) times more likely to have PD than their female counterparts (p = 0.012). Ethnic groups other than Muslims tend to be associated with PD more often and carry more than 8-fold (95% CI of OR: 8.4 – 37.2) higher risk of having the condition (p = 0.001). Likewise, other occupants were nearly 2(95% CI of OR: 0.98 – 3.74) times more prone to have PD than the students (p = 0.056).Conclusion: Personality Disorders are highly prevalent among people with OCD which remains underdiagnosed & under-addressed. Male OCD patients, non-Muslims and occupants other than students are more prone to have PD. Persons with Personality Disorders are far more likely to refuse psychiatric help and deny their problems.Ibrahim Card Med J 2017; 7 (1&2): 44-50